Preparation of PPy-WO3 Nano-composite for Supercapacitor Applications - Hameed, Firas J.; Ibrahim, Isam M. (Iraqi Journal of Science, 2021)
In this work, polypyrrole (PPy) composites were chemically prepared by a chemical oxidation method. Also, Tungsten Trioxide (WO3) nanoparticles were prepared and added in certain proportions to PPy. The structure properties were studied for the polypyrole and tungesten trioxide separately before mixing them together. The X-ray diffraction (XRD) analysis revealed a hexagonal WO3 and a triclinic PPy. It was observed that the nano-composite prepared by the addition of WO3 with 10 and 20% volume ratios to PPy shows a triclinic phase with the presence of hexagons. The molecular structures of PPy, WO3, and PPy–WO3 nano composites were depicted by Fourier-transform infrared spectroscopy (FTIR) in the scope of 400–4000 cm-1. The supercapcitors of PPy and PPy-WO3 were examined by calculating the figure of merit of the electrode (PPy and PPy-WO3) using cyclic voltammetry (CV), galvanostatic charge and discharge (GCD), and electrochemical impedance spectroscopy (EIS) techniques. It was found that the highest value of capacity (266.62 F/g) is obtained at 20% WO3 ratio.